2021
DOI: 10.1186/s12872-020-01823-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic nomogram for 30-day mortality of deep vein thrombosis patients in intensive care unit

Abstract: Background We aimed to use the Medical Information Mart for Intensive Care III database to build a nomogram to identify 30-day mortality risk of deep vein thrombosis (DVT) patients in intensive care unit (ICU). Methods Stepwise logistic regression and logistic regression with least absolute shrinkage and selection operator (LASSO) were used to fit two prediction models. Bootstrap method was used to perform internal validation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Compared with the serum creatinine, BUN was a better index to reflect the DKA severity. Previous studies have also revealed that high BUN levels are correlated with poor prognosis in ICU patients 24 25 . As high BUN was also found to be related to the poor prognosis of patients with acute heart failure, acute respiratory disease syndrome, and hepatic decompensation 26 27 28 , BUN might reflect the degree of injury of multiple important organs, which were also an important risk factor of critically ill patients.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Compared with the serum creatinine, BUN was a better index to reflect the DKA severity. Previous studies have also revealed that high BUN levels are correlated with poor prognosis in ICU patients 24 25 . As high BUN was also found to be related to the poor prognosis of patients with acute heart failure, acute respiratory disease syndrome, and hepatic decompensation 26 27 28 , BUN might reflect the degree of injury of multiple important organs, which were also an important risk factor of critically ill patients.…”
Section: Discussionmentioning
confidence: 95%
“…BUN is usually regarded as an important indicator of blood volume. Although many patients with DKA are complicated with acute renal failure, dehydration is the most common state among patients with DKA due to hypovolemia and hypotension Accepted Manuscript also revealed that high BUN levels are correlated with poor prognosis in ICU patients [24,25]. As high BUN was also found to be related to the poor prognosis of patients with acute heart failure, acute respiratory disease syndrome, and hepatic decompensation [26][27][28], BUN might reflect the degree of injury of multiple important organs, which were also found to be an important risk factor of critically ill patients.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Candidate clinical variables were selected based on published studies, accessibility, and professional knowledge. [7][8][9][10][11]18,19 We collected the basic information (gender, body mass index [BMI], smoking, previous history of VTE, etc. ), laboratory data (preoperative PSA, postoperative D-Dimer, postoperative PLT, coagulation index, T stage, etc.…”
Section: Data Collectionmentioning
confidence: 99%
“…SAB model includes sepsis, the maximum of anion gap and the minimum of bicarbonate. Sometimes the treatment of infection is insufficient, which may lead to organ dysfunction or sepsis (25,26). Sepsis significantly increases the length of hospital stay and mortality in ICU patients.…”
Section: Atmentioning
confidence: 99%